Management of Status Epilepticus - Lamsal, Ritesh; Bista, Navindra R. (Journal of Neuroanaesthesiology and Critical Care, 2019)
Status epilepticus (SE) is a life-threatening neurologic condition that requires immediate assessment and intervention. Over the past few decades, the duration of seizure required to define status epilepticus has shortened, reflecting the need to start therapy without the slightest delay. The focus of this review is on the management of convulsive and nonconvulsive status epilepticus in critically ill patients. Initial treatment of both forms of status epilepticus includes immediate assessment and stabilization, and administration of rapidly acting benzodiazepine therapy followed by nonbenzodiazepine antiepileptic drug. Refractory and super-refractory status epilepticus (RSE and SRSE) pose a lot of therapeutic problems, necessitating the administration of continuous infusion of high doses of anesthetic agents, and carry a high risk of debilitating morbidity as well as mortality.
Keywords: convulsive status epilepticus; neurocritical care; nonconvulsive status epilepticus; refractory status epilepticus; status epilepticus; super-refractory status epilepticus